Ciri iklim sekolah berkesan: Implikasinya terhadap motivasi pembelajaran - Ahmad Zabidi Abdul Razak, (penerbit ukm, 2006)
The objective of this study is to determine the climate characteristics of the effective schools. This study examines the perceptions of 97 teachers from four religious secondary schools in Selangor where the survey method is used. Frequencies and mean are used in data analysis. The study reveals that the characteristics of effective religious secondary school climate are (1) the application of Islamic way of life in every aspect of learning and work, (2) practicing ‘muraqabah’ that is the feeling that Allah is watching every action performed, (3) the school principal practices open communication when communicating with teachers and students, (4) teacher’s commitment towards school is high, (5) teachers cooperate to solve problems, (6) school compound is clean, beautiful, safe and there are ample classrooms being built, and (7) students’ behaviour at a satisfactory level. Based on the findings from this study, this article discusses the implication towards learning behaviour in schools.